Funding Conditions, Asset Prices and Macroeconomic Dynamics: Some U.S. Evidence - Matilde Vassalli; Carmine Trecroci (ZBW – Leibniz Information Centre for Economics, 2013)
Funding liquidity, i.e., the ease with which firms, investors and consumers can obtain funding, is a key property of today's monetary transmission mechanism. We investigate empirically the role played by various measures of credit availability in shaping the dynamics of asset prices and the fluctuations of real activity in the US.We find that changes in funding conditions are more tightly associated with future asset valuations than with developments in key macroeconomic aggregates. Results also point to the presence of a positive feedback loop between asset valuations and credit availability. Finally, the response of equity and house prices to the easing of funding conditions is stronger following shocks to liquidity than after conventional interest-rate shocks. These novel results highlight potentially destabilizing properties of recent liquidity cycles and unconventional monetary policies.
Keywords: E44; E51; G1; 330; Business cycle; Asset prices; Funding liquidity; Monetary policy